2009
DOI: 10.1159/000238304
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Changes of Anti-Elastin Antibodies in Senescence-Accelerated Mice

Abstract: Background: Antibodies recognizing the elastin precursor tropoelastin (ATEAb) or degradation products α-elastin (AEAb) are found in the serum of healthy human subjects, as a part of a homeostatic mechanism which assembles new or clears altered elastin structures. Serum ATEAb (reflecting elastin synthesis) and AEAb (reflecting elastin destruction) appear to correlate with the production and breakdown of the elastic tissue, respectively. Objective: The aim of this study was to investigate plasma levels of AEAb a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…It is well known that autoantibody titers increase with age and with smoking (29,35). In fact, antielastin antibodies have been considered a marker of aging in animal models (36). Yet, we think that this does not invalidate our results because FEV 1 and DL CO were expressed as percentage of the reference value and were, therefore, age-corrected, and smoking status was included in the multivariate analysis specifically.…”
Section: Strengths and Limitationsmentioning
confidence: 81%
“…It is well known that autoantibody titers increase with age and with smoking (29,35). In fact, antielastin antibodies have been considered a marker of aging in animal models (36). Yet, we think that this does not invalidate our results because FEV 1 and DL CO were expressed as percentage of the reference value and were, therefore, age-corrected, and smoking status was included in the multivariate analysis specifically.…”
Section: Strengths and Limitationsmentioning
confidence: 81%
“…A prior study demonstrated that female mice have higher anti-elastin antibody levels than males, which is consistent with our data. 18 The authors suggested that reproductive organ remodeling in female mice may be the cause of this finding, although this does not sound plausible in our subjects. Previous studies on the association between diabetes mellitus and antibody levels did not show consistent results.…”
Section: Discussionmentioning
confidence: 63%
“…Surprisingly, our results indicate that minoxidil tend to slightly increase IMT, and decrease distensibility. Exploring the renin angiotensin system [14], elastin gene transcription and its signaling pathway [45] and potential new biomarkers [47], we are hopeful to better explain how minoxidil influences biologically the elastogenesis in patients with WBS. Differences between groups in vessel wall thickening of 0.02 mm was very small.…”
Section: Discussionmentioning
confidence: 99%